Analysis of the short-term effect of three different level pedicle screws in the treatment of thoracolumbar type A fractures - Alimujiang Yusufu; Abudula Abulaiti; Abuduwupuer Haibier; Junyi Ma; Yuan Ma (Journal of Orthopaedic Surgery and Research)
Abstract Objective The effects of three short-segment vertebral fixation methods—short-segment fixation (4s group), short-segment fixation across the injured vertebra (6s group), and long-segment fixation (8s group)—on the surgical efficacy of patients with type A thoracolumbar fractures were compared to identify the optimal fixation method. Methods Data from 277 patients who underwent posterior pedicle screw fixation for thoracolumbar fractures between September 2018 and January 2023 were retrospectively analyzed. Surgery-related indicators, laboratory parameters, clinical functional measures (VAS and ODI), and postoperative imaging findings were compared among the three groups. Results Baseline data showed no significant differences among the three groups. The operation time in the 4s group (75.352 ± 15.458 min) and intraoperative blood loss (188.65 ± 42.728 ml) were significantly lower compared to the 8s group (operation time: 108.243 ± 19.529 min; intraoperative blood loss: 209.93 ± 50.542 ml), with statistically significant differences (p < 0.05). Postoperative hematocrit (33.277 ± 4.639) and albumin levels (34.971 ± 4.116) in the 6s group were significantly higher than those in the 8s group (hematocrit: 31.820 ± 4.323; albumin: 33.170 ± 3.553), with p < 0.05. Other outcome indicators did not show statistically significant differences (p > 0.05). Conclusion Short-segment fixation across the injured vertebra (6s) provides results comparable to short-segment fixation (4s) while causing less trauma. Furthermore, the 6s method demonstrates similar efficacy to long-segment fixation (8s) in maintaining long-term deformity correction. These findings offer valuable insights for clinicians in selecting surgical fixation methods, optimizing treatment strategies, and improving patient outcomes.